BS ISO 23678-4. Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats (including free-fall lifeboats) and rescue boats (including fast rescue boats), launching appliances and release gear. Part 4. Level 2 in-field competence (25th August 2021) - British Standards Institution
No abstract available